Ambulatory Blood Pressure Monitoring in the Elderly - Juan Diego Mediavilla García; Fernando Jaén Águila; Celia Fernández Torres; Blas Gil Extremera; Juan Jiménez Alonso (International Journal of Hypertension)
The incidence of hypertension is high in the elderly and is present in 2/3 of the patients older than 65 years. Prevalence can reach 90% in patients older than 80 years. The presence of isolated systolic hypertension (ISH) is characteristic of this population. However, the prevalence of hypertension by ambulatory blood pressure monitoring (ABPM) is not well known. In this study, we analyzed the special characteristics of hypertension in this population, giving special emphasis on ABPM readings.